CLINICAL SIGNIFICANCE OF NOVEL BIOMOLECULES SUCH AS GALECTIN-3, APOPTOSIS-INDUCING FACTOR, ENDOTHELIN, AND VEGF-A IN THE DIAGNOSIS OF CHRONIC HEART FAILURE - Almammadov, F.C. (World of Medicine and Biology, 2025)
The use of molecular biomarkers, alongside classical clinical and instrumental methods, is becoming increasingly relevant for the early diagnosis and prognosis of chronic heart failure. The study aimed to assess the diagnostic value of novel biomarkers (galectin-3, apoptosis-inducing factor, endothelin, and VEGF-A) by comparing their levels across various functional stages (I–II, III, IV) of chronic heart failure. The study involved 219 patients aged between 34 and 89 years who were diagnosed with CHF and examined and treated at the Clinical Medical Center between 2018 and 2024. The concentrations of the biomarkers galectin-3, AIF, endothelin, and VEGF-A in the blood serum were analyzed using the enzyme-linked immunosorbent assay (ELISA) method. More pronounced changes in the levels of the studied biomarkers were observed in patients with NYHA class IV chronic heart failure. In this group, compared to patients in NYHA class I, the concentration of AIF increased by 80 % (p